2020
DOI: 10.5812/iji.108958
|View full text |Cite
|
Sign up to set email alerts
|

CRP Levels in Viral Hepatitis: A Meta-Analysis Study

Abstract: Context: Viral hepatitis is a common infectious disorder with a high degree of mortality. The host immunological feedback to the hepatitis virus is dim and unable to down-regulate and clear infection. C-reactive protein (CRP), an acute phase reactant synthesized by hepatocytes in response to inflammatory reactions, facilitates apoptosis and phagocytosis. An effort has been made in the current meta-analysis study to elucidate the relationship between CRP and hepatitis B virus (HBV) and hepatitis C virus (HCV) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…For instance, Moura et al (2019) suggested that hepatitis viral replication inhibits CRP production and is unrelated to HBsAg positivity (Zhiping et al, 2020). However, several studies have demonstrated elevated CRP and PCT levels in various liver diseases, such as hepatitis, liver carcinoma, and liver cirrhosis (Bhuiyan et al, 2019;Zheng et al, 2018;Igna et al, 2022;Yuan et al, 2013;Tan et al, 2018;Singh et al, 2021;Kang et al, 2021;Chen et al, 2020;Lu et al, 2021). Thus, our findings are consistent with the findings of studies supporting a significant association between inflammatory markers and hepatitis B.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, Moura et al (2019) suggested that hepatitis viral replication inhibits CRP production and is unrelated to HBsAg positivity (Zhiping et al, 2020). However, several studies have demonstrated elevated CRP and PCT levels in various liver diseases, such as hepatitis, liver carcinoma, and liver cirrhosis (Bhuiyan et al, 2019;Zheng et al, 2018;Igna et al, 2022;Yuan et al, 2013;Tan et al, 2018;Singh et al, 2021;Kang et al, 2021;Chen et al, 2020;Lu et al, 2021). Thus, our findings are consistent with the findings of studies supporting a significant association between inflammatory markers and hepatitis B.…”
Section: Discussionsupporting
confidence: 92%
“…However, it is important to note that this study does not provide insights into the underlying reasons for these sex differences. Further research is needed to explore the mechanisms contributing to the observed sexspecific variations in CRP and PCT levels in the context of HBV infection [21] [22].…”
Section: Discussionmentioning
confidence: 99%
“…Old data have shown that CRP seems to be undetected in hepatitis C, and recent evidence has demonstrated that the pooled mean CRP level was within the normal range in cases with hepatitis C; however, it was higher in hepatitis B cases, suggesting that CRP expression correlates with hepatitis B disease progression, but not in chronic hepatitis C, and there is also a possibility that cytokine-mediated response is more pronounced in chronic hepatitis B compared to chronic hepatitis C [ 938 , 939 , 940 ]. Yet, it was previously reported that anti-CRP autoantibodies have been reported in hepatitis C cases, a fact that raises further diagnostic questions for its lower levels in that condition.…”
Section: Current Evidence On C-reactive Protein and Potential Conditionsmentioning
confidence: 99%